A Mathematical Approach to Optimize Security Crisis Management and Strengthen National Defense in DKI Jakarta Province - Anandari, Anatansyah Ayomi; Wadjdi, Achmad Farid; Harsono, Gentio (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to apply military mathematical models in decision making for security crisis management in DKI Jakarta Province. This research departs from the urgent need to deal with crime problems and improve regional security. Regression model is used to analyze the relationship between independent variables (Pure Participation Rate, Unemployment, Gini Index, and GRDP) and dependent variable (Criminal Risk). Historical and current data on security, education, employment, income inequality, and the economy were collected for analysis. The results show that Net Enrolment Rate and Unemployment have a negative influence on Criminal Risk, while Gini Index and GRDP have a positive influence. These findings provide a deeper understanding of the factors that contribute to the security crisis in the region. Based on the analysis results, this study concludes that the application of military mathematical models can be an important reference for the government in addressing the crime problem and improving security in DKI Jakarta Province. The proposed recommendations are to improve access to education, reduce the unemployment rate, address income inequality, and strengthen the economic sector. The implementation of integrated policies between government agencies is also considered important to achieve optimal results in overcoming the security crisis.